'Eradication was a dirty word': Anti-gambiae campaign, between cooperation and rivalry (1938–1940). Issue 1 (2nd January 2023) - Lopes, Gabriel; Cueto, Marcos
ABSTRACT: This article analyzes the efforts of the International Health Division of the Rockefeller Foundation (IHDRF) in its project initiative that resulted in the extermination of the African mosquito Anopheles gambiae from Brazil in 1940. This species, which originated in Dakar, Senegal, was identified in the Brazilian city of Natal in 1930, where insufficient local emergency sanitation actions enabled it to spread into the interior of the Brazilian northeast, causing an unprecedented malaria epidemic in the Americas in 1938, after years of silent spread. We will analyse the formation of Brazil's Malaria Service of the Northeast (MSNE), discussing its political and scientific controversies and how the transition from the idea of extermination to the idea of eradication was consolidated in the political process of creating this successful sanitation campaign. In addition, we will discuss how the integration and transnational development of medical entomology at the time was a fundamental factor in the cooperation and challenges among scientists involved in this campaign. The international cooperation of scientists, albeit oriented towards the project of eradication of this mosquito, organised different research agendas and gained new insights into the global dissemination of mosquito-borne diseases.